Assessing China's skills gap and inequalities in education - Molnar, Margit (OECD Economics Department Working Papers, 2015)
In recent years, many tertiary graduates have had difficulties finding a job, while factories have been struggling to recruit workers. Notwithstanding rapidly increasing education attainment, graduates' skills do not seem to match those demanded by the market. Moreover, structural changes in the economy aggravate the shortage of skills in newly emerging industries. While the problem is widely recognised, empirical studies of the issue are scarce and the skills gap has not been quantified. This paper aims at gaging the skills and knowledge gap of tertiary graduates of universities and vocational colleges across China. It also looks at the employment and wage prospects of graduates with different educational backgrounds. Inequalities in educational opportunities, stemming in particular from the urban-rural divide and to a lesser extent from the social background, shape careers and lives. The best primary and middle schools are located in the biggest cities and until recently children competed for a place at such schools. In third and fourth-tier cities or in rural areas, in contrast, there are fewer choices and thus less chance to get into a "model" high school or a top university. The family background also tends to have an impact on the choice of a school or profession and on future earnings. This paper discusses various aspects of inequalities related to the place of upbringing, family background and geographical area. Micro-level data analysis is complemented by an investigation into inequalities of various aspects of education at the city and county levels. This Working Paper relates to the 2015 OECD Economic Survey of China www.oecd.org/eco/surveys/economic-survey-china.htm